[?6-2-(2-Methylbenzoyloxy)ethyl methacrylate]bis(?6-1,2,4,5-tetramethylbenzene)tri-?-hydrido-?3-oxo-triruthenium(II)(3 Ru-Ru) tetrafluoroborate - Vieille-Petit, Ludovic; Therrien, Bruno; Buryak, Andrey; Severin, Kay; Süss-Fink, Georg (My University, 2004)
The trinuclear arene-Ru cluster cation, [Ru3H3(O)(C10H14)2(C14H16O4)]+, was synthesized and crystd. as the tetrafluoroborate (BF4-) salt. Crystals of the salt are monoclinic, space group P21/c, with a 13.592(3), b 17.817(4), c 15.066(4) Å, ? 100.238(3)°; Z = 4, dc = 1.713; R = 0.039, Rw(F2) = 0.087 for 8673 reflections. The cations form, along the b axis, infinite 1-dimensional chains through ?-stacking interactions. [on SciFinder(R)]
Keywords: ruthenium methylbenzoyloxyethyl methacrylate methylbenzene hydro oxo fluoroborate prepn structure; crystal structure ruthenium methylbenzoyloxyethyl methacrylate methylbenzene hydro oxo fluoroborate; mol structure ruthenium methylbenzoyloxyethyl methacrylate methylbenzene hydro oxo fluoroborate